KONTRIBUSI INTERAKSI GURU DAN SISWA MENGGUNAKAN ALAT PERAGA MINI ZOO TERHADAP HASIL BELAJAR - Nureva; Aulia Gustia Citra (STKIP Al Islam Tunas Bangsa dan HEPI Korda Lampung, 2019)
The purpose of this study was to determine the contribution of student teacher interaction contributions and the learning process of science using teaching aids both together and individually to student learning outcomes by using mini zoo props. The study was conducted using a correlational research approach of 210 people. Sampling technique with stratified proportional random sampling with a sample of 30 people. Data were collected through questionnaires and documentation which were then analyzed using the product moment correlation formula. This study found that: (1) there was a positive contribution between teacher-students amounting to 0.484 to learning outcomes. (2) there is a positive relationship between the learning process of 0.447 on learning outcomes. (3) there is a positive relationship of 0.539 between the student teacher and the learning process together on learning outcomes. The results prove that learning motivation and learning methods both together or individually have a significant positive contribution to learning outcomes by using mini zoo props. Keywords: interactions, mini zoo props, and learning outcomes